2016
DOI: 10.1111/ppa.12523
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure and fungicide resistance of Botrytis cinerea in pear orchards in the Western Cape of South Africa

Abstract: Botrytis cinerea isolates from pear blossoms (Pyrus communis) in South Africa were collected from four orchards in two production areas in the Western Cape. The cryptic species status based on vegetative‐incompatibility alleles of the Bc‐hch gene indicated that all the isolates belonged to B. cinerea. A microsatellite analysis of B. cinerea populations was performed to assess the genetic population structure. Total gene diversity (H) was high, with a mean of 0.69 across all populations. Some genotype flow was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…A high level of genotypic diversity was found among the B. cinerea populations isolated from grapevine in northern Italy, as obtained by other researchers on strains isolated from different hosts in several countries (Karchani‐Balma et al ., ; Fekete et al ., ; Walker, ; Wessels et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A high level of genotypic diversity was found among the B. cinerea populations isolated from grapevine in northern Italy, as obtained by other researchers on strains isolated from different hosts in several countries (Karchani‐Balma et al ., ; Fekete et al ., ; Walker, ; Wessels et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, the vineyard area A, which is completely isolated from the other regions by mountains, showed significant differences with the southern populations for several parameters such as the TE frequencies, higher genetic differentiation, lower gene flow, higher percentages of fludioxonil resistance and different percentages of strains resistant to cyprodinil and fludioxonil. Weak but significant geographical differentiation has also been detected at a regional scale by other authors in Europe (Walker et al ., ) and in Africa (Karchani‐Balma et al ., ; Wessels et al ., ). The mating type ratios, the low clonal fraction and the high genotypic diversity observed in this study, indicate that Lombard populations of B. cinerea could undergo regular recombination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results also suggest that the environmental reservoirs are probable sources of inoculum. Previous reports of the genetic diversity of B. cinerea from wild plants (e.g., primrose, bramble, dandelion, Hypochaeris radicata , Plantago lanceolata , and Sonchus asper ), illustrated the potential reservoirs of inoculum for crops on wild plants and weeds in agricultural systems (Fournier and Giraud, 2008; Rajaguru and Shaw, 2010; Walker et al, 2015; Wessels et al, 2016), but there have been no studies on non-agricultural sources. Phylogenetic comparisons of strains from crop plants and from environmental substrates presented in this study revealed that strains from crops and from the environment could not be distinguished, thereby supporting the hypothesis that strains from these different sources mix.…”
Section: Discussionmentioning
confidence: 99%
“…S. sclerotiorum populations on different crops in the United States showed prevalent clonality and some evidence of recombination (Aldrich-Wolfe et al 2015;Dunn et al 2017). A high level of genetic diversity but nonrandom mating was observed in B. cinerea populations in California (Ma and Michailides 2005) and South Africa (Wessels et al 2016), suggesting the absence or infrequent sexual reproduction, that was instead supposed to occur in other areas on various hosts, like Hungarian vineyards (Váczy et al 2008).…”
Section: Discussionmentioning
confidence: 99%